The concept of vulnerability and its relation to equality in the context of human rights: cases from climate change, anti-discrimination and asylum - Mayrhofer, Monika; Ammer, Margit; Wladasch, Katrin (Frontiers in Sociology, 2025)
The article analyzes the concept of vulnerability and its relation to the principles of equality and non-discrimination based on a theoretical discussion and the analysis of the concept in three case studies in different human rights areas. First, an overview of the development of the legal norms of the right to equality and non-discrimination in the context of social and political developments is given, including contextualizing and embedding the concept of vulnerability in this debate. Second, the results of three case studies from different policy and legal fields will be presented. The first case study focuses on the role of vulnerability in UN human rights documents on climate change and mobility, the second case study on the role of vulnerability in the anti-discrimination case law of European courts, and the third case study on the concept of vulnerability in Austrian asylum procedures. The objective is to study the concept in different settings and, subsequently, comparatively carve out common themes across the case studies. The case studies show that vulnerability is a fuzzy concept, which often ends up being attached to ‘special-needs groups’ and which frequently mobilizes stigmatizing and stereotyping narratives. The concept does not have equality-promoting connotations, emphasizes individual and group-specific deficit accounts, and often fails to grasp structural factors of discrimination and inequality.